Catalytic pathways for N-arylation of benzimidazoles: A comprehensive review - Anila Ghulam; Tooba Jabeen; Sana Aslam; Matloob Ahmad; Magdi E.A. Zaki (Results in Chemistry)
The N-arylated benzimidazoles are important structural motifs in many biologically active compounds. Due to their distinct physicochemical and structural features, they have applications in a wide range of domains, including pharmaceutical chemistry, material sciences, and catalysis. Synthetic chemists have devised a variety of methods to accomplish efficient N-arylation of benzimidazoles. Transition metal-based catalysis has emerged as a key strategy, utilizing metals such as copper (Cu), palladium (Pd), iron (Fe), nickel (Ni), iridium (Ir), and ruthenium (Ru). These catalysts, which are frequently supported by a variety of ligands, allow for the selective and efficient production of N-aryl bonds under a wide range of reaction conditions. Cross-coupling reactions, such as the Chan-Lam, Ullmann, and Buchwald-Hartwig protocols, are commonly used due to their durability and scalability. Metal-free techniques offer ecologically friendly options, and multicomponent reactions provide the benefit of convergent synthesis. Microwave-assisted reactions and photocatalyzed procedures have improved the efficiency, selectivity, and sustainability of N-arylation reactions. The review provides a comprehensive overview of the recent advancements and strategies employed in constructing this important class of heterocyclic compounds, highlighting their versatility and significance.